The Use of Pinterest-Based Mood Boards in Illustration Learning at SMP Negeri 2 Panongan, Tangerang - Azzahra, Alyaa Shabrina; Sobandi, Bandi; Santosa, Hery (Journal Research of Social Science, Economics, and Management, 2026)
One of the problems that often arise in learning illustration in junior high school is that students’ work tends to be uniform and less original, especially when they don’t have adequate visual references before they start drawing. The purpose of this study is to analyze whether the use of Pinterest-based mood boards can be a solution to encourage visual exploration, creativity, and learning motivation among grade VIII students at SMP Negeri 2 Panongan, Tangerang. This qualitative case study involved 35 students who were divided into five groups. Data was collected using an illustrative assessment rubric (covering visual and technical aspects) and a 25-item Likert self-assessment questionnaire, covering Pinterest experience, creativity, motivation, mood board effectiveness, and collaboration. The results showed that the use of Pinterest-based mood boards effectively supports students’ visual exploration, creativity, and learning motivation. The average score across all five groups was 79.2 out of 100, with four of the five groups exceeding the minimum passing score of 70. The results of the questionnaire showed that 82.8% of students gave positive responses, with no negative responses recorded. These findings show that Pinterest, as a digital mood board medium, is quite effective in helping students develop more diverse and focused visual ideas in cultural arts learning. The conclusion of this study emphasizes that the use of Pinterest-based mood boards can function both as a method and as a learning resource to inspire works of art.